Capitalis - Бородянский, Ю.; Саенко, Ю. (Социология: теория, методы, маркетинг, 2005)
The subject of this article is the thesis about capitalis as an attributive fiture that distinguishes human being from the animal kingdom. In Latin capitalis means the “head”. It is assumed that the Spirit laid capitalis in a human being as the first principle, instinctus of material and spiritual expansion. The economic interpretation of capitalis known as capital is a particular aspect.